Peran Transparansi Laporan Keuangan kepada Pihak Eksternal dalam Meminimalisir Asimetri Informasi - Novi Alvionita; Alisya Cahya Kamila; Lusianti Lusianti; Santi Alfitri; Ratna Febriyanti (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the impact of financial statement transparency in minimizing information asymmetry. Financial statement transparency is crucial in reducing information asymmetry between company management and external parties. Information asymmetry arises when management possesses more complete information, potentially leading to decisions detrimental to external stakeholders. Financial statements prepared in accordance with accounting standars such as IFRS or GAAP provide accurate and relevant information, supported by additional disclosures and independent external audits ,which enhhance stakeholder trust. Therefore, transparency not only reuces information asymmetry byt also support the principles of good corporate governance to foster a fair and sustainable bussiness environment.